2017
DOI: 10.1007/s12012-017-9400-8
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Ozone Therapy on Oxidative Stress, Cardiac Functions and Clinical Findings in Patients with Heart Failure Reduced Ejection Fraction

Abstract: The aim of study was to determine the effects of ozone therapy on the oxidative stress, cardiac functions and clinical findings in patients with heart failure reduced ejection fraction (HFrEF). A total of 40 patients with New York Heart Association 2 and 3 HF with left ventricular ejection fraction (LVEF) <35%, and 40 subjects without HF as control group were included in the study. Patients with HFrEF were given additional ozone therapy of major and minor administrations along with conventional HF treatment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…The systemic application only means ozone autohemotherapy (OAHT). Studies have found that ozone can induce and activate the body's antioxidant enzyme system to produce superoxide dismutase (SOD), which can remove part of the free radicals produced in the inflammatory reaction and interfere with the inflammatory factors produced in the process of disease development [7]. In animal experiments, it has been found that low-dose ozone can improve the level of blood lipid and inhibit oxidative stress to alleviate the progress of atherosclerotic diseases [8].…”
Section: Introductionmentioning
confidence: 99%
“…The systemic application only means ozone autohemotherapy (OAHT). Studies have found that ozone can induce and activate the body's antioxidant enzyme system to produce superoxide dismutase (SOD), which can remove part of the free radicals produced in the inflammatory reaction and interfere with the inflammatory factors produced in the process of disease development [7]. In animal experiments, it has been found that low-dose ozone can improve the level of blood lipid and inhibit oxidative stress to alleviate the progress of atherosclerotic diseases [8].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ozone was used for the first time to disinfect operating rooms in 1856 and subsequently for water treatment in 1860 34568. So far, data have shown that ozone could improve several diseases such as abscesses,910 acne,11 eczema,12 psoriasis,13 human immunodeficiency virus and acquired immune deficiency syndrome,14151617 fibromyalgia,18 arthritis,19 asthma,20 cancers,721 inflammation,22 cardiac disease,23 liver disorders,2425 uveitis,26 cystitis,27 chronic wounds,28 dyslipidemia,29 osteomyelitis,30 Raynaud’s disease,31 sepsis,32 and sinusitis 33…”
Section: Introductionmentioning
confidence: 99%
“… 10 Future effects can show O 3 therapy being used to treat heart failure. 11 Furthermore, there is growing evidence that O 3 can be used to treat DFUs. A study showed that O 3 treatment via rectal insufflation can improve glycemic index along with preventing oxidative stress in diabetic rats.…”
Section: Introductionmentioning
confidence: 99%